Klasifikasi Desa/Kelurahan di Kabupaten Gianyar: Ekstraksi dan Klasifikasi Potensi Wisata - Handayani, Mirah P; Suciptawati, Putu; Darmayanti, Trisna; Kencana, Eka N (Jurnal Master Pariwisata (JUMPA); Volume 07, Nomor 02, Januari 2021DO - 10.24843/JUMPA.2021.v07.i02.p19, 2021)
Tourism potential is one of the primary sources of destination development. Generally, there are three types of tourism potential that form tourist attractions. These potentials are (a) natural potential, (b) socio-cultural potential, and (b) artificial potential. Regarding destination sustainability, the uniqueness of villages' potentials is the primary factor to consider. This paper aims to identify the tourism potential of 70 villages in Gianyar Regency, Bali Province that spread over seven districts. The primary data collected from 170 respondents from August to September 2020, proportionally distributed over 70 villages. They were asked their opinion about the village's potential to be developed as a tourist village. The factors extracted from village tourism potential indicators were obtained by factor analysis and is used to form a tourism village cluster. The clustering showed three village groups, each consisting of 13, 24, and 33 villages. Keywords: classification, cultural tourism, factor analysis, village tourism